Suplementasi bakteri probiotik meningkatkan performa pertumbuhan dan efisiensi pakan benih ikan mas (Cyprinus carpio). - Mudeng, Cindy C.; Manoppo, Henky; Lantu, Sartje; Kreckhoff, Reni L.; Tumbol, Reiny A. (e-Journal BUDIDAYA PERAIRAN, 2020)
Probiotic from carp intestines and its effects on increasing growth performance and feed efficiency had been investigated. Fish used were carp fingerlings weighing 2.33 g  in average. The fish were taken from the Tatelu Freshwater Aquaculture Fisheries Center.  Probiotics used were isolated from the intestines of carp. Before running the experiment, the fish were acclimatized for 10 days under laboratory conditions. During acclimatization the fish were fed commercial pellets without the addition of probiotics. The dose of feeding was 5% /bw/day, 2 times a day at 09:00 am and 16:00 pm. Furthermore, fish are stocked in 15 aquariums each measuring 60x40x40cm3 with a density of 20 fish/aquarium. Each aquarium was equipped with aeration and water pumps for recirculation. Uneaten feed and feces were removed through siphoning. Water exchange was done every 2-3 days.  After acclimatization, the fish were fed with pellet supplemented with probiotic at  concentration of A: without addition of probiotic; B: 1 x 106 cfu /mL; C: 1 x 107 cfu / mL; D: 1 x 108 cfu / mL; E: 1 x 109 cfu/mL. The fish were fed twice a day with feeding dose of 5% /bw/ day, for 21 days. Data collected consisted of daily growth rates, growth rates, feed efficiency and feed conversion ratio. The results of research showed that the addition of probiotics in feed had a very significant effect on growth, feed efficiency, and feed conversion ratio (P <0.01) with the best results achieved in administering probiotics as much as 1 x 108 cfu / mL. In conclusion, probiotic bacteria originating from the intestines of carp can be used to improve the growth performance of the fish itself.